2021
DOI: 10.1364/josab.433873
|View full text |Cite
|
Sign up to set email alerts
|

Design of high extinction ratio, low loss, and compact optical modulators and switches based on GST phase change material

Abstract: In this paper, an electrically driven optical modulator and switch based on micro-ring resonators using the phase change material (PCM) of G e 2 S b 2 T e 5 (GST) is designed and their optical properties are investigated. The change in refractive index between two states in PCMs is orders of magnitude larger than conventional electro-optic and free-carrier dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As reported by Mahmoodi et al , the device figure of merit is maximized by high extinction ratio resulting from optimizing the thin film dimensions. 64…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Mahmoodi et al , the device figure of merit is maximized by high extinction ratio resulting from optimizing the thin film dimensions. 64…”
Section: Resultsmentioning
confidence: 99%
“…Compared with previous studies reviewed above, [90,91] both the extinction ratio and insertion loss performances have been improved. In 2021, a 1 × 2 silicon integrated optical switch with GST was further proposed by Mahmoodi et al [96] The structure is shown in Figure 15. In this design, instead of depositing PCM on top of the silicon waveguide [90,91] or adding an additional PCM-loaded waveguide, [94] a sector of the silicon microring is replaced with a GST-filled slot waveguide.…”
Section: Silicon Integrated Optical Switches With Pcm Based On the Mr...mentioning
confidence: 99%
“…The SiN layer is used to planarize and protect the silicon surface. A microheater is further added on top of the VO 2 layer laterally, and [96] ).…”
Section: Silicon Integrated Optical Switches With Pcm Based On the Wa...mentioning
confidence: 99%
“…Moreover, GST demonstrates a decent endurance: about 10 6 cycles (10 11 in phase change memories [36]), which can be improved by doping (N, C, Zn) [37]. However, for the desired spectral region, GSTbased optical modulator is less-explored although rigorously studied for 1.5 µm communication band [38][39][40].…”
Section: Introductionmentioning
confidence: 99%